ANALISIS PEMENUHAN HAK ANAK BERDASARKAN FIKIH ḤAḌĀNAH - Na'imin; Mifchan Solichin, Nur; Nuraini, Diah (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
Underage marriage in Kedu Subdistrict is still a complex social issue, with the main focus on the fulfillment of children's rights, especially the ḥaḍānah aspect of Wahbah Az-Zuhaili. This research uses a qualitative approach through field research methods, with data collection techniques in the form of in-depth interviews, participatory observation, and documentation of eleven early-age couples registered at the Kedu District KUA for the 2020-2023 period. The results showed that although the couples did not formally understand the fiqh of ḥaḍānah, they practiced parenting based on instinct, social support, and gradual adaptation. The main challenges faced include limited education, economic pressure, and emotional immaturity, but no divorce cases were found in this group of subjects. This finding indicates the potential for successful parenting in underage marriages with the right support. This research emphasizes the importance of a contextualized socio-religious approach and ongoing coaching to strengthen the quality of parenting from a fiqh perspective.